Current developments in biotechnology and bioengineering biochar towards sustainable environment - Ngo, Huu Hao (Elsevier, 2023)
"The primary concern of environmental sustainability is to: (i) reduce use of physical and depletable resources; (ii) recycle and use renewable resources; (iii) redesign the production process to eliminate the production of toxic materials and protect the environment. Biochar, as a renewable material, can be produced from various sustainable biomass feedstocks through pyrolysis technologies. Biochar Towards Sustainable Environment highlights the contribution of biochar to environmental sustainability. The book provides a detailed overview of the sustainable biomass wastes feedstocks and different technologies for biochar production, and its sustainable applications in various aspects."